Quality Analysis of Virgin Coconut Oil Resulting From a Combination of Fermentation and Controlled Heating Using Silica by Rice Husk Ash - Rahmadani, Fahdila; Harimu, La; Rahmanpiu, (Hydrogen: Jurnal Kependidikan Kimia, 2026)
Virgin Coconut Oil (VCO) has unique characteristics such as a very clear color resembling mineral water, low water and free fatty acid content, and high lauric acid content. The purpose of this study was to compare the quality of physical, chemical, and organoleptic parameters of VCO before and after adsorption with rice husk ash silica. The method used was adsorption. The adsorbent is arranged to a height of 4 cm with a flow rate of 14 drops per minutes. The results showed that the clarity test before and after adsorption was 85.8% and 97.9%. The water content before and after adsorption was 0.29% and 0.07%; free fatty acids were 0.49% and 0.17%; peroxide value was 1.98 mg eq/kg and 1.48 mg eq/kg; and saponification value was 189.34 mg KOH/g and 229.24 mg KOH/g. The average organoleptic color test before and after adsorption was 3.07 and 4; ordor was 3.33 and 3.2; and tastes 2.8 and 2.4, meet SNI 7381:2008 and SNI 2015. Thus, it can be concluded that rice husk ash silica can improve the quality of VCO.